2008
DOI: 10.1002/hipo.20473
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of dorsal and ventral hippocampus to trace and delay fear conditioning

Abstract: Trace conditioning relies on the maintained representation of a stimulus across a trace interval, and may involve a persistent trace of the conditioned stimulus (CS) and/or a contribution of contextual conditioning. The role of hippocampal structures in these two types of conditioning was studied by means of pretraining lesions and reversible inactivation of the hippocampus in rats. Similar levels of conditioning to a tone CS and to the context were obtained with a trace interval of 30 s. Neurotoxic lesions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 78 publications
(119 reference statements)
5
70
1
Order By: Relevance
“…Importantly, in the present study, we replicated our previous findings that ventral hippocampal muscimol impairs contextual fear conditioning in both foreground and background procedures, while not significantly affecting tone fear conditioning (Bast et al, 2001a), and we showed similarly selective effects on contextual fear conditioning for dorsal hippocampal muscimol infusions. In the present study, the effects of dorsal hippocampal muscimol on contextual fear conditioning was not totally reliable, with this effect failing to reach significance in Experiment 3; this is consistent with the variable results reported in the literature, with some studies reporting significant disruption of contextual fear by dorsal hippocampal muscimol (Esclassan et al, 2009;Wang et al, 2012), while others failed to find a significant effect (Maren & Holt, 2004;Matus-Amat et al, 2004). Interestingly, the selective impairment of contextual, but not tone, fear conditioning by hippocampal muscimol resembles the selective anterograde deficits in contextual fear conditioning following infusion of NMDA-receptor antagonists into the ventral (Zhang et al, 2001) or dorsal hippocampus Schenberg and Oliveira, 2008).…”
Section: Ventral and Dorsal Hippocampal Muscimol Impair Contextual Bsupporting
confidence: 90%
See 4 more Smart Citations
“…Importantly, in the present study, we replicated our previous findings that ventral hippocampal muscimol impairs contextual fear conditioning in both foreground and background procedures, while not significantly affecting tone fear conditioning (Bast et al, 2001a), and we showed similarly selective effects on contextual fear conditioning for dorsal hippocampal muscimol infusions. In the present study, the effects of dorsal hippocampal muscimol on contextual fear conditioning was not totally reliable, with this effect failing to reach significance in Experiment 3; this is consistent with the variable results reported in the literature, with some studies reporting significant disruption of contextual fear by dorsal hippocampal muscimol (Esclassan et al, 2009;Wang et al, 2012), while others failed to find a significant effect (Maren & Holt, 2004;Matus-Amat et al, 2004). Interestingly, the selective impairment of contextual, but not tone, fear conditioning by hippocampal muscimol resembles the selective anterograde deficits in contextual fear conditioning following infusion of NMDA-receptor antagonists into the ventral (Zhang et al, 2001) or dorsal hippocampus Schenberg and Oliveira, 2008).…”
Section: Ventral and Dorsal Hippocampal Muscimol Impair Contextual Bsupporting
confidence: 90%
“…Data transformations may help to improve compliance with these assumptions (Judd et al, 1995;Osborne, 2002). However, freezing data are commonly analyzed using ANOVA without any prior transformation of data, even though some authors have applied data transformation (e.g., Esclassan et al, 2009). Similarly, many elevated plus maze studies use ANOVA without prior data transformation (e.g., Bertoglio and Carobrez, 2002;Rezayat et al, 2005;Pohorecky, 2008), even though some studies also use nonparametric tests (e.g., Bannerman et al, 2004) or data transformation prior to ANOVA (e.g., Bertoglio et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations